PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 47 UNRA KECAMATAN AWANGPONE KABUPATEN BONE MELALUI PENGGUNAAN ALAT PERAGA DEKAK-DEKAK - Jafar, Muh. Idris Jafar; Sudarto, Sudarto; Khair, Asrar Abu Khair (Jurnal Cakrawala Ilmiah, 2024)
This research is a Classroom Action Research that aims to improve the mathematics learning outcomes of the third-grade students of SD Negeri 47 Unra through the application of Dekak-Dekak ​​teaching aids. The subjects of this study were of the 9 people of the third-grade students at SD Negeri 47 Unra. The action plan in this study consisted of two cycles with four stages, namely : planning, implementation, observation and reflection. The data collection techniques used were observation and testing. The data analysis techniques used were qualitative and quantitative techniques. The results of the study showed that there was an increasing in the students' mathematics learning outcomes from cycle I (sufficient qualification) to good qualification in cycle II. The conclusion of this study is that the application of Dekak-Dekak ​​teaching aids can improve the mathematics learning outcomes of the third-grade students of SD Negeri 47 Unra, Awangpone District, Bone Regency.